Influence of microwave sterilization on the cutting capacity of carbide burs - Laiza Maria Grassi Fais; Lígia Antunes Pereira Pinelli; Gelson Luis Adabo; Regina Helena Barbosa Tavares da Silva; Caroline Canhizares Marcelo; Dalton Geraldo Guaglianoni (University of São Paulo, 2009)
OBJECTIVE: This study compared the cutting capacity of carbide burs sterilized with microwaves and traditional sterilization methods. MATERIAL AND METHODS: Sixty burs were divided into 5 groups according to the sterilization methods: dry heat (G1), autoclave (G2), microwave irradiation (G3), glutaraldehyde (G4) or control - no sterilization (G5). The burs were used to cut glass plates in a cutting machine set for twelve 2.5-min periods and, after each period, they were sterilized (except G5) following the protocol established for each group. The cutting capacity of the burs was determined by a weight-loss method. Data were analyzed statistically by Kruskal-Wallis and Dunn's test. RESULTS: The means of the cutting amount performed by each group after the 12 periods were G1 = 0.2167 ± 0.0627 g; G2 = 0.2077 ± 0.0231 g; G3 = 0.1980 ± 0.0326 g; G4 = 0.1203 ± 0.0459 g; G5 = 0.2642 ± 0.0359 g. There were statistically significant differences among the groups (p<0.05); only dry heat sterilization was similar to the control. CONCLUSION: Sterilization by dry heat was the method that least affected the cutting capacity of the carbide burs and microwave sterilization was not better than traditional sterilization methods.